2016
DOI: 10.1158/0008-5472.can-15-2377
|View full text |Cite
|
Sign up to set email alerts
|

CD271 Expression on Patient Melanoma Cells Is Unstable and Unlinked to Tumorigenicity

Abstract: The stability of markers that identify cancer cells that propagate disease is important to the outcomes of targeted therapy strategies. In human melanoma, conflicting data exist as to whether hierarchical expression of CD271/p75/NGFR (nerve growth factor receptor) marks cells with enriched tumorigenicity, which would compel their specific targeting in therapy. To test whether these discrepancies relate to differences among groups in assay approaches, we undertook side-by-side testing of published methods of pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Previous studies indicate that CD271 expression within primary melanomas correlates with a more aggressive tumour phenotype and reduced patient survival, while isolated CD271‐expressing cells from primary melanomas initiate tumour growth in immunocompromised NRG mice at a higher rate than CD271 – cells . Conversely, other studies suggest that, rather than being a marker of distinctive melanoma‐initiating subpopulations, CD271 expression is induced during acquired resistance to BRAF inhibition, DNA‐damaging drugs or ethanol . Collectively, these studies indicate that CD271 is a biomarker of tumour progression and is consistent with the concept that CD271 signalling constitutes a stress‐tolerance mechanism within tumour cells.…”
supporting
confidence: 77%
“…Previous studies indicate that CD271 expression within primary melanomas correlates with a more aggressive tumour phenotype and reduced patient survival, while isolated CD271‐expressing cells from primary melanomas initiate tumour growth in immunocompromised NRG mice at a higher rate than CD271 – cells . Conversely, other studies suggest that, rather than being a marker of distinctive melanoma‐initiating subpopulations, CD271 expression is induced during acquired resistance to BRAF inhibition, DNA‐damaging drugs or ethanol . Collectively, these studies indicate that CD271 is a biomarker of tumour progression and is consistent with the concept that CD271 signalling constitutes a stress‐tolerance mechanism within tumour cells.…”
supporting
confidence: 77%
“…CD271 expression - like other melanoma markers - underlies phenotype switching responsible for fluctuations of CD271 expression 44 , 50 . We demonstrated that A375 cells with stable over expression of CD271 are indeed capable of migration in brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…The assay identifies all classes of genetic alterations, including base substitutions, insertions, and deletions. 19 …”
Section: Methodsmentioning
confidence: 99%